Effects of organic and inorganic fertilizers on lettuce (Lactuca sativa L.) and soil properties (SAARC Journal of Agriculture, 2018)
A Greenhouse experiment was conducted to identify the suitable dose of organic fertilizer for lettuce production. Different doses of organic fertilizer (6.5, 13 and 26 t ha-1) and the recommended dose of chemical fertilizer (RDCF) as standard were selected for this experiment. Application of 13 t ha-1 organic fertilizer significantly increased leaf size (length and breadth) of lettuce. This treatment also increased 14, 25, 21, 32, 24, 27, 36 and 168% fresh weight, dry weight, N, P, K, Ca, Mg & Na uptake over RDCF, respectively. Organic matter content was increased of 17.79, 43.82 and 89.89% in 6.5, 13 and 26 t ha-1 organic fertilizer treated plots respectively over recommended dose of chemical fertilizers. Data also indicated that organic fertilizer @ 26 t ha-1 resulted in significant increase in pH, total nitrogen (24%), organic matter (90%) and Zn (29%) compared to RDCF and decreased electrical conductivity, mineral nitrogen (NH4 +-N & NO3 --N) and cadmium and lead (Cd & Pb) in soil. Positive and significant correlation was observed on yield and yield attributes of lettuce and soil nitrogen, organic matter with pH, total nitrogen with mineral nitrogen and negative correlation was found with applied organic fertilizer with cadmium and lead. Based on these results, organic fertilizer @ 13 t ha-1 without chemical fertilizer could be recommended to increase lettuce yield as well as mitigate heavy metals in soil.SAARC J. Agri., 15(2): 93-102 (2017)